Pengaruh Industri Gula Aren Terhadap Tingkat Kesejahteraan Rumah Tangga Di Desa Mopolo Kecamatan Ranoyapo - Pusung, Rizky A.; Tumbel, Tinneke M.; Punuindoong, Aneke Y. (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
Palm sugar is one of the most important food needs for daily needs in the household and food and beverage industries, both large and small. The activity of making palm sugar has long been carried out by the people of Mopolo Village, even some of them have carried out these activities for decades. Palm sugar is not only consumed by itself but also for sale. High economic value is one of the factors for brown sugar makers. The palm sugar industry is located in Mopolo Village, Ranoyapo District, Minahasa Selatan District North Sulawesi. Mopolo Village has a land area after expansion of approximately 1700 ha. ’'The Effect of the Palm Sugar Industry on the Household Welfare Levels of Industrial Owners in Mopolo Village, Ranoyapo District" has the formulation of the problem whether the Palm Sugar industry has an effect on the household welfare level of industrial owners in Mopolo Village, Ranoyapo District.This study aims to determine the effect of the Palm Sugar industry on the level of household welfare of industrial owners in Mopolo village, Ranoyapo. District. The object of this study is the owner of palm sugar industry in mopolo village, Ranoyapo sub-district, south Minahasa Sulawesi in the north.The results of hypothesis testing showed that industrial variables had a positive and significant effect on the level of household welfare of industrial owners. This study was the first study on palm sugar industry in mopolo village, Ranoyapo sub-district, minsel North Sulawesi.